FDI and the Skill Premium : Evidence from Emerging Economies - Cruz, Marcio (World Bank, Washington, DC, 2018)
Foreign direct investment may play an important role in transferring technologies from high-income to emerging economies, which can lead to uneven effects on the wages of skilled and unskilled workers. This paper combines project-level data on greenfield foreign direct investment with household surveys to estimate the effects of foreign direct investment on the wage skill premium across sectors and regions in seven emerging economies (Brazil, Colombia, Ethiopia, Mexico, the Philippines, South Africa, and Vietnam). The results suggest that foreign direct investment is associated with a higher probability of employment and higher wages for unskilled workers, relative to skilled workers, in six of the seven countries analyzed in this paper. Moreover, the effects of foreign direct investment on wages are relatively larger for unskilled women.